Estudo anatômico do circuito arterial do encéfalo em Eira barbara – relato de dois casos. - Breno Costa de Macedo; Érika Branco; Luiza Corrêa Pereira; Ana Rita de Lima (Biotemas)
http://dx.doi.org/10.5007/2175-7925.2014v27n2p177